2017
DOI: 10.3168/jds.2016-12442
|View full text |Cite
|
Sign up to set email alerts
|

Fertility traits of Holstein, Brown Swiss, Simmental, and Alpine Grey cows are differently affected by herd productivity and milk yield of individual cows

Abstract: Milk yield has a strong effect on fertility, but it may vary across different herds and individual cows. Therefore, the aim of this study was to assess the effects of breed and its interaction with level of milk production at the herd level (Herd-L) and at a cow-within-herd level (Cow-L) on fertility traits in dairy cattle. Data were gathered from Holstein (n = 17,688), Brown Swiss (n = 32,697), Simmental (n = 27,791), and Alpine Grey (n = 13,689) cows in northeastern Italy. The analysis was based on records f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
6
21
0
1
Order By: Relevance
“…Our results showed that, after correcting the data for all the other confounding factors, cows reared on farms characterized by a higher mean level of milk production had on average a better conception rate than cows reared on farms with lower productivity (Figure 1). In a similar study carried out in a different environment (mountainous areas with lower milk production levels), we found a tendency for a curvilinear response, with a reduction of average conception rate increasing the mean herd milk yield up to 20 to 25 kg/d and an improvement of conception rate increasing further mean herd milk yield level to 30 to 35 kg/d (Toledo-Alvarado et al, 2017). These tendencies were more pronounced in dual-purpose breeds, such as Simmental, and less evident in specialized dairy breeds, such as Holstein-Friesian and Brown Swiss.…”
Section: Effects Of Herd and Cow Productivity On The Conception Rate Of The Cowssupporting
confidence: 67%
“…Our results showed that, after correcting the data for all the other confounding factors, cows reared on farms characterized by a higher mean level of milk production had on average a better conception rate than cows reared on farms with lower productivity (Figure 1). In a similar study carried out in a different environment (mountainous areas with lower milk production levels), we found a tendency for a curvilinear response, with a reduction of average conception rate increasing the mean herd milk yield up to 20 to 25 kg/d and an improvement of conception rate increasing further mean herd milk yield level to 30 to 35 kg/d (Toledo-Alvarado et al, 2017). These tendencies were more pronounced in dual-purpose breeds, such as Simmental, and less evident in specialized dairy breeds, such as Holstein-Friesian and Brown Swiss.…”
Section: Effects Of Herd and Cow Productivity On The Conception Rate Of The Cowssupporting
confidence: 67%
“…There are many studies showing the negative correlation between high milk yield and reproduction performance (Lucy 2001;Dobson et al 2008;Walsh et al 2011). These results are in parallel with international studies in which milk yields of two breeds are compared (Micinski et al 2014;Janzekovic et al 2009;Budimir et al 2011;Toledo-Alvarado et al 2017). At national literature, on the other hand, there is no reference study where these two breeds are compared for milk yields.…”
Section: Resultsmentioning
confidence: 77%
“…is points to reproductive shortfalls compared with other studies [29,30]. Farms with low pregnancy rates (first service and cumulative) at individual animal level had the highest NSP.…”
mentioning
confidence: 72%